On Music and War - Morag Josephine Grant (Transposition)
The musicology of war and collective violence is a relatively young field, and appropriate theoretical frameworks for this research are still emerging. Here, an approach is outlined which, in keeping with the programme for music sociology outlined by Christian Kaden, is both systematic and historical in its approach. Perspectives from the sociology of violence (Randalls Collins, Charles Tilly) can help us understand the dynamics of collective violence, and thus the role of music within it. War is a cultural rather than natural phenomenon, and music plays significant roles in the rituals which enable wars to happen.